The study of account receivable in Bank Kerjasama Rakyat, Masai Branch / Nur Irma Suriani Md Yusoff - Md Yusoff, Nur Irma Suriani (Faculty of Business and Management, 2009)
Account Receivable is the money which is owed to a company by a customer for products and services provided on credit. This is treated as a current asset on a balance sheet. A specific sale is generally only treated as an account receivable after the customer is sent an invoice. Loan or credit given to the customer are reflected in accounts receivable so credit policy in Bank Kerjasama Rakyat is a guideline to the bank in managing their account receivable. when account receivable not manages carefully, it can create increasing in non-performing loan and bank facing difficult in collecting their account receivable. The objective of this case study is to see the performance of non-performing loan, disbursement and collection from 2007 until 2009, to compared the relation between non-performing loan with disbursement and to determined courses in not managing account receivable carefully. Information from primary data and secondary data are gathered through interview, observation, internet sources and journal. The findings of this study is account receivable still have some weaknesses even thought the profit or performance shown increasing every year, Increasing non-performance loan consider good if the figure not more that disbursement figure. Lastly, the reschedule offered by bank can decreasing non-performing loan amount.